2011
DOI: 10.1152/japplphysiol.01390.2010
|View full text |Cite
|
Sign up to set email alerts
|

Trans-spinal direct current stimulation modulates motor cortex-induced muscle contraction in mice

Abstract: The present study investigated the effect of trans-spinal direct current (tsDC) on the firing rate, pattern, and amplitude of spontaneous activity of the tibial nerve and on the magnitude of cortically elicited triceps surae (TS) muscle contractions. The effect of combined tsDC and repetitive cortical electrical stimulation (rCES) on the amplitude of cortically elicited TS twitches was also investigated. Stimulation was applied by two disk electrodes (0.79 cm(2)): one was located subcutaneously over the verteb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
89
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(100 citation statements)
references
References 71 publications
11
89
0
Order By: Relevance
“…In general, following spinal cord injury, increased excitation and reduced inhibition of the mechanisms controlling motoneurons causes abnormal generation of force (Roy and Edgerton, 2012). We previously showed that dorsal surface anodal stimulation of the spinal cord decreases spinal excitability, while cathodal stimulation increases excitability (Ahmed, 2011). This agrees with previous studies, despite differences in location of the return electrode (Fuortes, 1954;Eccles et al, 1962).…”
Section: Introductionsupporting
confidence: 90%
See 1 more Smart Citation
“…In general, following spinal cord injury, increased excitation and reduced inhibition of the mechanisms controlling motoneurons causes abnormal generation of force (Roy and Edgerton, 2012). We previously showed that dorsal surface anodal stimulation of the spinal cord decreases spinal excitability, while cathodal stimulation increases excitability (Ahmed, 2011). This agrees with previous studies, despite differences in location of the return electrode (Fuortes, 1954;Eccles et al, 1962).…”
Section: Introductionsupporting
confidence: 90%
“…The general procedure has been used previously by our laboratory (Ahmed, 2011(Ahmed, , 2013aAhmed and Wieraszko, 2012), and the experimental setup is shown in Figure 1A. Animals were anesthetized using ketamine/xylazine (90/10 mg/kg, i.p.).…”
Section: Methodsmentioning
confidence: 99%
“…Plantarflexion movements were increased in amplitude, duration, and slope, but not latency. This was most likely due to increased TS muscle force produced by c-tsDC stimulation (Ahmed, 2011;Ahmed and Wieraszko, 2012). Dorsiflexion movements showed decreased latency and increased amplitude and slope, but no change in duration.…”
Section: Discussionmentioning
confidence: 92%
“…Trans-spinal direct current (tsDC) stimulation is a neuromodulatory technique that causes immediate and long-term changes in spinal cord excitability (Aguilar et al, 2011;Ahmed, 2011Ahmed, , 2013Cogiamanian et al, 2011;Truini et al, 2011;Ahmed and Wieraszko, 2012;Cogiamanian et al, 2012;Lamy et al, 2012;Lamy and Boakye, 2013). The overarching goal of tsDC stimulation is to restore function that has been lost due to spinal cord or brain injuries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation